Association between food insecurity, ethnicity, and mental health in the UK: An analysis of the Family Resource Survey - Maddy Power; Tiffany Yang; Katie Pybus; Benham Tajik (PLoS ONE, 2025)
The study aimed to assess the relationship between food insecurity and ethnicity in the United Kingdom (UK), and to explore how the relationship between food insecurity and mental health varies by ethnic group. Data from the 2019/20 Family Resource Survey provided information on ethnicity, presence of long-standing illnesses affecting mental health, and food security assessed using 10-item Adult Food Security module. Logistic regression was used to assess the relationship between food security status and degree of anxiety and presence of long-standing illness affecting mental health. Analyses were adjusted for covariates and stratified by ethnicity. Participants were a representative sample of private UK households (N = 19,210), using the Household Reference Person as the main respondent. The majority of the sample were food secure (87%), identified as White (90.7%), and 22% reported a long-standing illness affecting mental health. Food insecurity was associated with longstanding illness affecting mental health (adjusted OR 2.01 (1.70, 2.39)) among all ethnic groups; Asian/Asian British respondents reported the highest odds of having a longstanding illness affecting their mental health (OR=2.63 (1.05, 6.56)). The study finding of an association between food insecurity and mental health for all UK ethnic groups, but one which is stronger for ethnic minority groups, necessitates a population-wide response alongside targeted interventions.